Providing a General Model for the Successful Implementation of Digital Transformation in Organizations - Haidar Ahmadi; Najme Parsaei; Seyyed Hamed Hashemi; Hamidreza Nematollahi (مدیریت دولتی)
Objective Purpose: Digital transformation involves the comprehensive integration of digital technologies into all facets of an organization's operations, fundamentally altering the manner in which the organization functions and delivers value to its stakeholders. This research seeks to identify critical factors in order to develop a generalized model for the successful implementation of digital transformation across various organizational contexts. Methods This study adopts an interpretive and inductive approach and is practical in its objectives. It is conducted as qualitative research, designed as a single-section time study, and is categorized as part of broader field research. The participants of this research are professors and specialists in the fields of digital transformation and management, carefully selected through purposeful sampling to ensure they meet specific criteria that qualify them to provide insightful information. Data collection was primarily conducted through semi-structured interviews with 15 individuals until theoretical saturation was achieved. To further enrich the data, text studies and thematic analysis methods were employed for categorizing and coding the collected data.